Colocaciones y captaciones relacionadas con el sector productivo de la Caja Huancayo, agencia Iquitos, 2016 - 2021 - Shapiama Cordova, Maroly Sofia (2023)
sector the general objective of the study was to know the placements and fundraising related to the productive sector of Caja Huancayo, Iquitos agency, 2016-2021. In relation to its methodology, the research was quantitative with descriptive design, the population and sample was integrated by the reports and records where relevant information on placements and fundraising is exposed, the sampling was non-probabilistic by convenience, the technique used to collect data was the documentary analysis, the instrument applied was the analysis guide. As a result, the item of loans related to the productive sector that obtained the highest amount was business loans, which was equivalent to S/110,464.62, while the item of deposits related to the productive sector that obtained the highest amount was time deposits, which was equivalent to S/77,705.69. It was concluded that the placements and fundraising related to the productive sector of Caja Huancayo, Iquitos agency, 2016-2021, are positive because they reflect a continuous increase because, by 2021, the amount was S/41,429.06 and S/31,649.42 for placements and fundraising respectively.